Fourier Transform Infrared Spectrophotometry-Partial Least Square for Simultaneous Quantification of Paracetamol, Guaifenesin, Phenylpropanolamine, and Chlorpeniramine Maleate in Tablet - Tarigan Rida Evalina; Melya Sukma; Lisda Rimayani Nasution (Asian Journal of Pharmaceutical Research and Development, 2025)
The aim of this research is to develop a method usingFourier Transform Infrared Spectrophotometry-Partial Least Square (FTIR-PLS) for the simultaneous analysis of Paracetamol (PA), Guaifenesin (GU), Phenylpropanolamine (PH), and Chlorpheniramine Maleate (CH) in tablet. The method in this research was to create calibration and validation model using FTIR-PLS, where the wavenumbers for quantitative analysis of PA, GU, PH, and CH are respectively 1625-1575 cm-1, 1280-1230 cm-1, 1615-1565 cm-1, and 1709-1575 cm-1. The results of this research are the R2 values ​​for calibration and validation for PA, GU, PH, CH are 0.967, 0.965, 0.970, and 0.964 respectively. Root Mean Square Error Of Cross Validation (RMSECV) PA, GU, PH and CH were 0.0362, 0.0415, 0.1372 and 0.0141 respectively. Prediction Sum Of Residual Squared Errors (PRESS) PA, GU, PH and CH are 0.0328, 0.0431, 0.0470, and 0.005 respectively. FTIR-PLS has proven to be an effective method for the simultaneous quantification of PA, GU, PH, and CH in tablet.